Applied Research and public innovation: experiences in monitoring and evaluation of social programs within the partnership between DPU and PNUD (Simbiótica. Revista Eletrônica, 2026)
The article discusses recent experiences of applied social research within the scope of the Federal Public Defender's Office (DPU), carried out in partnership with the United Nations Development Program (UNDP) in 2024. Based on the experiences of monitoring and evaluating the Caravan of Rights in the Reconstruction of Rio Grande do Sul Program and the Program to Combat Political Gender Violence in the 2024 Municipal Elections, the text reflects on methodological challenges and possibilities for innovation in public contexts in the face of social emergencies. It argues that applied research, when guided by principles of international cooperation and a commitment to human rights, can act as a vector for institutional innovation, social inclusion, and democratic strengthening.
Keywords: applied social research; human rights; public policy; social inclusion; democracy